2007
DOI: 10.1111/j.1365-2141.2007.06525.x
|View full text |Cite
|
Sign up to set email alerts
|

FLT3/ITD expression increases expansion, survival and entry into cell cycle of human haematopoietic stem/progenitor cells

Abstract: SummaryActivating mutation of FLT3 by internal tandem duplications (ITDs) in the juxtamembrane region is the most common molecular aberration found in acute myeloid leukaemia (AML). In this study, a lentiviral vector containing two promoters achieved consistent and efficient co-expression of FLT3/ITD and GFP in transduced human CD34 + haematopoietic stem/progenitor cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 47 publications
3
26
0
Order By: Relevance
“…4I and J). Previous studies have shown that FLT3/ITD promotes cell growth and survival (40). Taken together, our results suggest that the activation of multiple signaling pathways is required for NIDF cells to induce AML (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…4I and J). Previous studies have shown that FLT3/ITD promotes cell growth and survival (40). Taken together, our results suggest that the activation of multiple signaling pathways is required for NIDF cells to induce AML (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…The concept of LSC also supports the hypothesis that class I mutations are secondary to class II mutations. 213,214 In agreement with this hypothesis is that some patients with FLT3 mutation at diagnosis relapse without mutation. 26,44 Another event implicated in leukemogenesis is the deregulation, in blast cells, of genes involved in the maintenance of the stem cell phenotype.…”
Section: Gene Mutations In Acute Myeloid Leukemiasupporting
confidence: 55%
“…46 Activating mutation of FLT3 have also been shown to increase expression of MYC in AMLs. 47 Hemizygous loss of APC detected in this work is known to cause aberrant activation of the WNT pathway in leukemia, 48,49 which may also lead to overexpression of MYC. EXT1 gene was found to be essential for the coordinated activation of WNT signaling during Drosophila development.…”
Section: Discussionmentioning
confidence: 99%